2019
DOI: 10.1126/science.aaw9032
|View full text |Cite
|
Sign up to set email alerts
|

Double PIK3CA mutations in cis increase oncogenicity and sensitivity to PI3Kα inhibitors

Abstract: Activating mutations in PIK3CA are frequent in human breast cancer, and phosphoinositide 3-kinase alpha (PI3Kα) inhibitors have been approved for therapy. To characterize determinants of sensitivity to these agents, we analyzed PIK3CA-mutant cancer genomes and observed the presence of multiple PIK3CA mutations in 12 to 15% of breast cancers and other tumor types, most of which (95%) are double mutations. Double PIK3CA mutations are in cis on the same allele and result in increased PI3K activity, enhanced downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
226
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(270 citation statements)
references
References 74 publications
(52 reference statements)
17
226
3
3
Order By: Relevance
“…S3). This thought-provoking observation, although only hypothesis-generating at this point given the small sample size, does echo one recently observed with PI3K inhibitors, where patients with double mutations in the same allele of PIK3CA resulting in hyperactivation of PI3K signaling and increased oncogenicity had enhanced sensitivity to therapy targeting PI3K ( 11 ). In our analysis, the presence of an AKT1 mutation remained important, however, as patients with PI3K pathway activation in the absence of a coincident AKT1 mutation seemed to fare the same on an mTOR inhibitor as patients without any hit in the pathway.…”
Section: Genomic Comparisonsupporting
confidence: 74%
“…S3). This thought-provoking observation, although only hypothesis-generating at this point given the small sample size, does echo one recently observed with PI3K inhibitors, where patients with double mutations in the same allele of PIK3CA resulting in hyperactivation of PI3K signaling and increased oncogenicity had enhanced sensitivity to therapy targeting PI3K ( 11 ). In our analysis, the presence of an AKT1 mutation remained important, however, as patients with PI3K pathway activation in the absence of a coincident AKT1 mutation seemed to fare the same on an mTOR inhibitor as patients without any hit in the pathway.…”
Section: Genomic Comparisonsupporting
confidence: 74%
“…This demonstrates the utility of PIK3CA-centric stratification, yet a substantial proportion of patients with PIK3CA-mutant tumours did not benefit from the BYL719 and fulvestrant combination [22]. Although recent studies demonstrated that double PIK3CA mutations in cis confer greater sensitivity to PI3Kα inhibition, these studies focused on inhibition of proliferation/growth [7,8]. Such parameters do not strictly correlate with dedifferentiation or 'stemness' which are more strongly linked with metastasis and ultimately death.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have recently shown that many PIK3CA-associated cancers harbour multiple independent mutations activating the PI3K pathway, including multiple PIK3CA mutations in cis or trans [3,[5][6][7][8]. We further reported that human induced pluripotent stem cells (iPSCs) with two endogenous alleles of the strongly activating cancer "hotspot" mutation PIK3CA H1047R exhibit pronounced phenotypic differences to isogenic cells heterozygous for the same PIK3CA variant [6].…”
Section: Introductionmentioning
confidence: 89%
“…The PI3K signaling pathway is involved in the biological processes of cellular proliferation, apoptosis, survival, motility, and metastasis (40,41). Mutation in PIK3CA is present in most solid tumors (42) and is found in 12-15% of patients with breast cancers (43). A recent study has shown that mutation in PIK3CA corresponds to a poor prognosis in patients with hormone receptorpositive metastatic breast cancer but a good prognosis in patients with triple-negative breast cancer (44).…”
Section: Discussionmentioning
confidence: 99%